Commonality Considerations in the Design of Flight Deck of Civil Aircraft. (November 2020) - Dong, Wenjun; Wang, Yuan; Li, Xianxue; Dong, Dayong
Abstract: Commonality in the flight deck can reduce development costs, shorten the time of operational courses e.g. transition time of pilots and expand the market, thus is becoming one of the most important features of modern civil aircraft design. Benefits from commonality in the flight deck was discussed in this paper as well as the aspects of commonality. Since commonality would bring significant benefits to the aircraft company and improve its profitability, more effort should be devoted to it.